Phosphoproteome analysis demonstrates the potential role of THRAP3 phosphorylation in androgen‐independent prostate cancer cell growth. Issue 7 (April 2016) - Ino, Yoko; Arakawa, Noriaki; Ishiguro, Hitoshi; Uemura, Hiroji; Kubota, Yoshinobu; Hirano, Hisashi; Toda, Tosifusa
Abstract : Elucidating the androgen‐independent growth mechanism is critical for developing effective treatment strategies to combat androgen‐independent prostate cancer. We performed a comparative phosphoproteome analysis using a prostate cancer cell line, LNCaP, and an LNCaP‐derived androgen‐independent cell line, LNCaP‐AI, to identify phosphoproteins involved in this mechanism. We performed quantitative comparisons of the phosphopeptide levels in tryptic digests of protein extracts from these cell lines using MS. We found that the levels of 69 phosphopeptides in 66 proteins significantly differed between LNCaP and LNCaP‐AI. In particular, we focused on thyroid hormone receptor associated protein 3 (THRAP3), which is a known transcriptional coactivator of the androgen receptor. The phosphorylation level of THRAP3 was significantly lower at S248 and S253 in LNCaP‐AI cells. Furthermore, pull‐down assays showed that 32 proteins uniquely bound to the nonphosphorylatable mutant form of THRAP3, whereas 31 other proteins uniquely bound to the phosphorylation‐mimic form. Many of the differentially interacting proteins were identified as being involved with RNA splicing and processing. These results suggest that the phosphorylation state of THRAP3 at S248 and S253 might be involved in the mechanism of androgen‐independent prostate cancer cell growth by changing the interaction partners.